BRIDGING BORDERS: THE IMPACT OF GLOBAL TRADE ON NIGERIA’S ECONOMIC DEVELOPMENT - Jaho Philip; Mojekwu, Ogechukwu Rita (American Journals, 2024)
This study examined the relationship between international trade and economic development in Nigeria from 1985 to 2022. Secondary data on per capita income, terms of trade, and exchange rates were collected from the Central Bank of Nigeria (CBN) statistical bulletin. The study utilized the Augmented Dickey-Fuller (ADF) unit root test and the Autoregressive Distributed Lag (ARDL) bounds test as the primary analytical techniques. The results from the ADF unit root test indicated that the variables were stationary at orders zero and one, which met the requirements for employing the ARDL bounds testing approach. The ARDL bounds test for cointegration revealed a long-run relationship among the variables. The short-run ARDL results demonstrated that terms of trade were positively related to per capita income, while the exchange rate exhibited an inverse relationship with per capita income. Based on these findings, it is recommended that the government implement policy measures aimed at expanding exports, as this has the potential for economies of scale. Additionally, the monetary authority should maintain a market-driven exchange rate policy to encourage local production, ultimately leading to an increase in the export of finished products and strengthening the Naira against the dollar.
Keywords: ARDL, Exchange rate, Income, Per capita, Term of trade.